The Role of the Code of Ethics to Improve professionalism of English Teachers - isti, Nuraqsa Istifarni; Indonesia, Hafizhatu Nadia; Nurul Azmi; Nusaindah Nurul Amin; Mhd Rayyan Fahadi (PEBSAS: Jurnal Pendidikan Bahasa dan Sastra, 2024)
This research explores the role and implementation of the Teacher Code of Ethics in increasing the professionalism of educators in Indonesia, exploring aspects of the attachment of religious values and norms in the context of Eastern culture. The main focus of this research is on the role of Islamic religious teachers, who are inherently expected to comply with the Code of Ethics as ethical foundation in the profession. Using a qualitative approach with literature analysis, this research explores theories that support the role of codes of ethics in the educational context in Indonesia. The National Education System Law and the definition of teachers as professional education personnel are the main basis. The results of this research are the need to instill awareness about the teacher code of ethics, continuous evaluation of its implementation, and efforts to increase professionalism through self-reflection on learning practices. Research also shows that implementing a code of ethics is the main key in realizing the common goal of improving the quality of education in Indonesia. By understanding and implementing a code of ethics, it is hoped that teachers can make a positive contribution to building a reputation and appreciation for their role in the world of education.